2009
DOI: 10.4161/cc.8.12.8741
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B kinase inhibition in mitosis: Strategies for optimizing the use of Aurora kinase inhibitors such as AT9283

Abstract: Aurora kinases play a key role in regulating mitotic division and are attractive oncology targets. AT9283, a multi-targeted kinase inhibitor with potent activity against Aurora A and B kinases, inhibited growth and survival of multiple solid tumor cell lines and was efficacious in mouse xenograft models. AT9283-treatment resulted in endoreduplication and ablation of serine-10 histone H3 phosphorylation in both cells and tumor samples, confirming that in these models it acts as an Aurora B kinase inhibitor. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
(40 reference statements)
0
54
0
Order By: Relevance
“…For this reason, the Aurora kinases are currently one of the most interesting targets for cancer therapy. Moreover, recent studies demonstrated that Aurora kinase inhibitors synergize with microtubule targeted agents to induce apoptosis in several tumor cell lines (56,57) and are potent killers of taxane-sensitive and -resistant ovarian cancer cells (58). Interestingly, our results show that ERp57 in the nucleus is phosphorylated and suggest the involvement of a specific kinase and/or phosphatase activity in the modulation of ERp57 subcellular distribution.…”
Section: Discussionmentioning
confidence: 49%
“…For this reason, the Aurora kinases are currently one of the most interesting targets for cancer therapy. Moreover, recent studies demonstrated that Aurora kinase inhibitors synergize with microtubule targeted agents to induce apoptosis in several tumor cell lines (56,57) and are potent killers of taxane-sensitive and -resistant ovarian cancer cells (58). Interestingly, our results show that ERp57 in the nucleus is phosphorylated and suggest the involvement of a specific kinase and/or phosphatase activity in the modulation of ERp57 subcellular distribution.…”
Section: Discussionmentioning
confidence: 49%
“…Floating and adherent cells were collected and treated as described previously. (34) Samples were resolved by SDS-PAGE and immunoblotted with antibodies specific for Akt, pAkt, androgen receptor, cleaved PARP, c-Met, EGFR, phospho-EGFR, Erk, phospho-Erk, S6, phospho-S6, Stat3, phospho-Stat3 (Cell Signaling Technologies, Cambridge, UK), B-Raf, CDK4, HER2 Raf-1 (Santa Cruz Antibodies, Santa Cruz, CA, USA), actin (Abcam, Cambridge, UK), HSP70 (StressGen Biotechnologies, Victoria, BC, Canada), or GAPDH (Chemicon International, Temecula, CA, USA). This was followed by infrared dye labeled anti-rabbit or anti-mouse antibodies (Licor Bioscience, Lincoln, NE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were prepared for analysis as described previously. (34) Quantification was by comparison with a standard calibration line. The limit of detection for AT13387 was 150 nM in blood and 120 nM in tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Drug AZD1152 is an aurora kinase inhibitor especially of Aurora kinase B. Aurora kinases are chromosomal passenger proteins, located near the spindle and help in various process of mitosis. It has been proved to be novel anticancer drug for acute leukemia [7][8][9][10][11].…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%